3a^2+-5a^2-ab+b^2-7ab-7b^2-3a^2合并同类项的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 05:38:23
3a^2+-5a^2-ab+b^2-7ab-7b^2-3a^2合并同类项的值3a^2+-5a^2-ab+b^2-7ab-7b^2-3a^2合并同类项的值3a^2+-5a^2-ab+b^2-7ab-7b
3a^2+-5a^2-ab+b^2-7ab-7b^2-3a^2合并同类项的值
3a^2+-5a^2-ab+b^2-7ab-7b^2-3a^2合并同类项的值
3a^2+-5a^2-ab+b^2-7ab-7b^2-3a^2合并同类项的值
3a^2+(-5a^2)-ab+b^2-7ab-7b^2-3a^2
=-5a^2-8ab-6b^2
如果不懂,祝学习愉快!
(a-b)^3+2ab(a-b)
化简:1.3a+2b-5a-b 2.3(-ab+2a)-2(3a-ab)
a^2b(a-b)-7ab(b-a)因式分解
(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg
已知a*a-ab=3,ab+b*b=-5,求代数式a*a+b*b与a*a-2ab-b*b的值
因式分解:a×a×a-2a×a×b+ab×b
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
a^2b-ab+2ab^2-5a^b-4ab+3ab^2化简快
a^2b^2-7ab+10.3a^3b-6a^2b-45ab.
1/4a^2b^2{3ab(a+b)-5a(ab-b^2)}=?
a^3-ab^2 =a (a^2 -b^2) =a(a+b)(a-b)
a(a-1)-(a×a-b)=-5,求(a×a+b×b)÷2-ab
3(-ab+2a)-(3a-b)
3(-ab+2a)-(3a-b)
a+b/2ab
2AB/A+B
a+b/2ab
6a-5b+2ab+5b-3a